2018
DOI: 10.1111/jcmm.14025
|View full text |Cite
|
Sign up to set email alerts
|

Exercise during transition from compensated left ventricular hypertrophy to heart failure in aortic stenosis rats

Abstract: We evaluated the influence of aerobic exercise on cardiac remodelling during the transition from compensated left ventricular (LV) hypertrophy to clinical heart failure in aortic stenosis (AS) rats. Eighteen weeks after AS induction, rats were assigned into sedentary (AS) and exercised (AS‐Ex) groups. Results were compared to Sham rats. Exercise was performed on treadmill for 8 weeks. Exercise improved functional capacity. Echocardiogram showed no differences between AS‐Ex and AS groups. After exercise, fracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 60 publications
1
29
0
2
Order By: Relevance
“…HF rat model [10] was prepared by abdominal aortic stenosis method. HF was induced by ligating abdominal aorta to create a cardiac load pot.…”
Section: Establishment Of Animal Modelmentioning
confidence: 99%
“…HF rat model [10] was prepared by abdominal aortic stenosis method. HF was induced by ligating abdominal aorta to create a cardiac load pot.…”
Section: Establishment Of Animal Modelmentioning
confidence: 99%
“…Eight weeks of running on a treadmill increased the weight of the left ventricle in rats in a prior study (22). Another study showed that six weeks of resistance training increased the weight of the rat's heart (23).…”
Section: Discussionmentioning
confidence: 90%
“…Phosphorylated MAPKs subsequently activate downstream substrates involved in cardiac hypertrophy, including c-Jun, activated transcription factor 2 and cardiomyocyte enhancer factor 2, and then regulate cellular gene transcription and protein synthesis, leading to cardiomyocyte enlargement and fibroblast proliferation in cardiac tissues (40,41). Although the role of p38 in cardiac hypertrophy remains largely elusive and controversial (42,43), ERK signaling is generally accepted to have a role in this pathology. The ERK1/2 cascade was observed in hypertrophic and failing mammalian hearts, while deletion of ERK (ERK1 −/− and ERK2 +/− ) did not cause any obvious reduction in the hypertrophic response to various stimuli (44,45).…”
Section: Discussionmentioning
confidence: 99%